Psychometric analysis of the critical thinking skills instrument in physics learning using the Rasch model - Noperi, Hendri; Diani, Rahma; Irwandani, Irwandani; Suryani, Yani; Sodikin, Sodikin; Saputro, Trimo (Indonesian Journal of Science and Mathematics Education, 2025)
Critical thinking is a core competency in physics learning, yet measuring it is constrained by a lack of psychometrically validated instruments. This study aims to develop and analyze a critical thinking assessment instrument on "Work and Simple Machines" for junior high school students. Using a Research and Development (R and D) approach, a 10-item essay instrument was trialed with 175 eighth-grade students and analyzed using the Rasch Model via WINSTEPS. Results indicate construct validity through unidimensionality (variance explained = 39.3%), item fit, and effective rating scale functioning. Reliability was good (student = 0.79; item = 0.84), with adequate separation values. The instrument is considered feasible, valid, and reliable as a diagnostic tool. This research provides educators with an objective tool to map students' weaknesses, enabling targeted pedagogical interventions and effective physics learning strategies.